EKSISTENSI PRODUK PIS BOLONG SEBAGAI MEDIA EDUKASI RELIGIUSITAS BUDAYA BALI BAGI WISATAWAN DI DESA KAMASAN, KLUNGKUNG - Putu Sabda Jayendra; I Wayan Eka Sudarmawan; Nyoman Surya Wijaya (Jurnal Ilmiah Hospitality Management, 2019)
Pis Bolong or uang kepeng is one of the cultural products that have religious values ​​in Bali. Hindus in Bali use pis bolong as a means of ceremonies and upakara in carrying out their religious ritual activities. Pis bolong has high religious, philosophical, historical and aesthetic values, so that it becomes one of the mainstay cultural products of Kamasan Village, Klungkung which is an attraction for foreign tourists. The rare phenomenon of pis bolong, besides its expensive price due to its scarcity, and the emergence of massive imitation holes which also contribute to its existence in the world of tourism. The feared impact is also a decrease in the understanding of foreign tourists about sacred and religious Balinese culture inspired by Hindu values. In this case, the pis bolong industry in Kamasan Village, Klungkung District, Klungkung Regency, Bali has a role as a media in educating tourists, especially foreign tourists about the religiosity of Balinese culture.